Trends in the incidence of asthma, atopic dermatitis, and multiple sclerosis before, during, and after the COVID-19 pandemic in a US claims database - Kexin Zhu; Julie Barberio; Nicole Tsao; Anil Mor; Venkatesh Harikrishnan; Xinyu Li; Sarah-Jo Sinnott (PLoS ONE, 2026)
There is limited evidence on how reduced healthcare resource utilization during the COVID-19 pandemic has affected the detection of inflammatory and immunologic diseases. We aimed to describe the observed incidence rates (IRs) of asthma, atopic dermatitis (AD), and multiple sclerosis (MS) before, during, and after the pandemic. Individuals aged ≥6 years were identified in Optum’s de-identified Clinformatics ® Data Mart Database from 2018 to 2022 to make 20 season-based cohorts. Age- and sex-standardized IRs of asthma, AD, and MS were estimated. Incidence rate ratios (IRR) and 95% confidence intervals (CI) were calculated comparing IRs in seasonal cohorts in 2019–2022 to the corresponding timeframe in 2018. Compared to spring 2018, IRs of asthma, AD, and MS in spring 2020 decreased by 14% (IRR: 0.86, 95% CI: 0.84–0.87), 28% (IRR: 0.72, 95% CI: 0.69–0.75), and 23% (IRR: 0.77, 95% CI: 0.68–0.87), respectively. The observed incidence reduction was most profound in children (6–11 years) and adolescents (12–17 years), followed by senior adults (≥65 years). There was no sex difference. IRs returned to or exceeded pre-pandemic levels for AD and MS in summer 2020 and for asthma in spring 2021. COVID-19 led to an apparent decline in incidence for selected inflammatory and immunologic diseases, which was more pronounced for pediatric and senior populations. The observed decrease in incidence likely reflects delayed access to healthcare, resulting in unrecorded (but still occurring) diagnoses for those time periods. Future studies using data that encompass the pandemic period should exercise caution in the design of study and interpretation of incidence or prevalence data.